Synergistic combination of electronic and electrical properties of SnO2 and TiO2 in a single SnO2-TiO2 composite nanofiber for dye-sensitized solar cells - Bakr, Zinab H.; Wali, Qamar; Jamil, Ismail; Elumalai, Naveen Kumar; Uddin, Ashraf; Rajan, Jose (Elsevier, 2018)
Tin dioxide (SnO2) and titanium dioxide (TiO2) are popular metal oxide semiconductors; they are explored for many applications because of their unique properties. This paper details that electronic and electrical properties of SnO2 and TiO2 can be synergistically combined in an one-dimensional nanostructure, such as electrospun nanofibers. The resulting composite nanofibers (CNFs) showed beneficial properties when used as a photoanode in dye-sensitized solar cells (DSSCs). In particular, the CNFs showed higher conduction band energy than SnO2 and higher electrical conductivity than TiO2. The SnO2-TiO2 CNFs are synthesized by electrospinning a polymeric solution containing equimolar concentration of tin chloride and titanium alkoxide precursors and subsequent annealing. The composite formation is demonstrated by X-ray diffraction and energy dispersive X-ray measurements and morphology by scanning electron microscopy. Synergy in electronic and electrical properties are demonstrated by cyclic voltammetry, absorption spectroscopy, and electrochemical impedance spectroscopy. Dye-sensitized solar cells fabricated using the CNFs as photoanode showed higher open circuit voltage and short circuit current density than those achieved using pure SnO2 and pure TiO2, respectively.